2010
DOI: 10.4049/jimmunol.1000589
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Contribute to the Mucosal Adjuvant Effect of CTA1–DD after IgG-Complex Formation

Abstract: Mast cell activation is one of the most dramatic immune-mediated responses the body can encounter. In the worst scenario (i.e., anaphylaxis), this response is fatal. However, the importance of mast cells as initiators and effectors of both innate and adaptive immunity in healthy individuals has recently been appreciated. It was reported that mast cell activation can be used as an adjuvant to promote Ag-specific humoral immune responses upon vaccination. In this study, we have used a clinically relevant mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…In the previous studies, nasal lavage IL-6 production was slightly increased in WT→KO mice given 0.25 or 4 μg IL-1α nasally and hematopoietic cell expression of IL-1R1 correlated with maximal adjuvant activity. Additionally, mast cells have been reported to be required for the maximal adjuvant activities of imiquimod[35] and CTA1-DD/IgG[34]. Therefore, we chose to evaluate the requirement for mast cells in the nasal adjuvant activity of IL-1α.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, nasal lavage IL-6 production was slightly increased in WT→KO mice given 0.25 or 4 μg IL-1α nasally and hematopoietic cell expression of IL-1R1 correlated with maximal adjuvant activity. Additionally, mast cells have been reported to be required for the maximal adjuvant activities of imiquimod[35] and CTA1-DD/IgG[34]. Therefore, we chose to evaluate the requirement for mast cells in the nasal adjuvant activity of IL-1α.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies have evaluated the roles of individual cell types in the response to adjuvant delivery using mouse strains with targeted mutations. While an absolute requirement has been demonstrated for mast cells in the adjuvant activity of imiquimod and CTA1-DD/IgG(intranasal and transcutaneous immunization, respectively) [34, 35], a previous study by Hou et al demonstrated that the adjuvant activity of systemically delivered CpG required adjuvant-responsive CD11c + cells for maximal adjuvant activity [36]. Elucidating the requirement for an adjuvant-responsive mucosal barrier following vaccination with one potent mucosal vaccine adjuvant, IL-1α, may provide insight into the role of the mucosal barrier and help identify cell types important in the generation of adaptive immune responses to mucosally delivered vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the roles of mast cells have been extended to providing adjuvanticity for vaccination. [2][3][4][32][33][34] We have come to recognize that greater levels of antigen-specific immune responses could be obtained when the mucosal adjuvant CTA1-DD, by virtue of its unspecific binding to immunoglobulins, was complexed with IgG forming immune complexes that could activate nasal CTMC. 4 In contrast, MMC failed to be activated by CTA1-DD/IgG immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mast cells have also been depicted in their potential to boost mucosal vaccination as mast cell activators are demonstrated to be powerful mucosal adjuvants . We have previously shown robust adjuvanticity exerted by Fc γ receptor‐mediated mast cell activation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation